Pretransplantation Inflammatory and Nutritional Status in Elderly Allogeneic Hematopoietic Stem Cell Transplantation: Prognostic Value of C-Reactive Protein-to-Albumin Ratio - Miyazaki, Takuya; Tachibana, Takayoshi; Suzuki, Taisei; Izumi, Akihiko; Fujimaki, Katsumichi; Sato, Shuku; Tamai, Yotaro; Michishita, Yusuke; Suzuki, Takahiro; Ishii, Ryuji; Hirasawa, Akira; Hashimoto, Chizuko; et al. (Transplantation and cellular therapy, 2024)
•Biomarkers were compared in elderly patients undergoing allogeneic HSCT.•C-reactive protein-to-albumin ratio (CAR) was the most useful prognostic indicator for HSCT in elderly patients.•CAR is a powerful patient-related risk factor independent of HCT-CI score. There are no clear criteria for selecting elderly patients with hematologic malignancies eligible for allogeneic hematopoietic stem cell transplantation (HSCT). This study aimed to evaluate inflammatory and nutritional status biomarkers as prognostic indicators of allogeneic HSCT in elderly patients. We compared the prognostic effects of 4 representative pretransplantation biomarkers: C-reactive protein-to-albumin ratio (CAR), Glasgow Prognostic Score (GPS), prognostic nutritional index (PNI), and albumin-to-globulin ratio (AGR). A total of 143 patients age ≥60 years who underwent their first allogeneic HSCT for a hematologic malignancy were enrolled between 2010 and 2020 in our single-center cohort. The median patient age was 65 years (range, 60 to 72 years). Pretransplantation high CAR, high GPS, and low PNI scores were associated with poor overall survival (OS), but the AGR was not associated with OS. Among the 4 biomarkers, CAR stratified OS most significantly (P < .001). Multivariate analyses identified only high CAR as an independent prognostic factor associated with OS (hazard ratio [HR], 1.98; P = .031) and showed that a Hematopoietic Cell Transplantation-Specific Comorbidity Index (HCT-CI) score ≥3 also was associated with OS (HR, 2.04; P = .012). High CAR was correlated with poor performance status, male sex, and high Disease Risk Index, but not with high HCT-CI score. When the patients were stratified into 3 groups according to a composite risk assessment using CAR and HCT-CI, the 3-year OS decreased significantly with increasing scores (82.8%, 50.3%, and 27.0%, respectively; P < .0001). In conclusion, CAR is the most useful prognostic indicator among the inflammatory and nutritional status biomarkers for allogeneic HSCT in elderly patients. Inflammatory and nutritional status in the elderly may be important prognostic factors for allogeneic HSCT independent of HCT-CI score.